Extinction and Decay Estimates of Solutions for a Class of Porous Medium Equations. (5th November 2007) - Liu, Wenjun; Wang, Mingxin; Wu, Bin
Abstract : The extinction phenomenon of solutions for the homogeneous Dirichlet boundary value problem of the porous medium equationu t = Δ u m + λ | u | p − 1 u − β u, 0 < m < 1, is studied. Sufficient conditions about the extinction and decay estimates of solutions are obtained by usingL p -integral model estimate methods and two crucial lemmas on differential inequality.